Active Fuelling of a Passenger Car Sized Pre-Chamber Ignition System with Gaseous Components of Gasoline - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2020)
Homogeneous lean or diluted combustion can significantly increase the efficiency of spark ignition engines. Active fuelled pre-chamber ignition systems can overcome the problem that common spark ignitions systems are incapable to ignite strongly diluted mixtures. A small portion of the charge is burned in a separated chamber, which is connected to the main chamber by multiple small orifices. The combustion inside the pre-chamber generates hot gases, which penetrate into the main chamber and ignite the diluted charge on multiple sites. Active pre-chamber ignition systems feature a separate fuelling or scavenging system in addition to the one of the main combustion chambers. Preferably, gaseous fuel is used for the pre-chamber fuelling allowing better dosing accuracy and mixture preparation inside the pre-chamber. Using the mixture of air and gasoline vapour present in the fuel tank above the liquid level for fuelling the pre-chamber is one key element enabling an active pre-chamber ignition system for passenger cars. An experimental setup was built to simulate a fuel tank under different environmental conditions. The composition of the gasoline vapour-Air-mixture inside the tank was analyzed for various industry known reference fuels under extreme conditions. The necessary concentration of hydrocarbons was accomplished with all tested fuels. Additionally, the system was integrated into a engine testbench to analyze the engine combustion depending on the pre-chamber fuelling. The dosing of gasoline vapour-Air-mixture into the pre-chamber is implemented via a solenoid valve together with a self-developed check valve. Investigations in the especially critical low-load range show stable engine combustion in all conditions if the dosed mass of the fuel vapor-Air-mixture is adapted to the concentration of hydrocarbons present in this mixture.
Created from Fastlane, Scopus look-up

Active Pre-chamber Ignition Systems: An Enabler for New ICE Combustion Concepts - Russwurm, Tim; Wensing, Michael (9th European Combustion Meeting (ECM2019), 2019)

Aktive Vorkammerzündung für Personenkraftwagen - Russwurm, Tim (Shaker Verlag, 2023)
Diese Arbeit beschreibt die Einsatzmöglichkeiten einer aktiven Vorkammerzündung in PKW-Ottomotoren. Vorkammerzündsysteme stellen eine Möglichkeit dar, Brennverfahren mit stark verdünnter Zylinderladung zu realisieren, indem die Zündenergie erhöht wird. Bei einer aktiven Vorkammer wird die Gemischzusammensetzung innerhalb der Vorkammer durch ein separates Dosierventil mit einem Kraftstoffdampf-Luft-Gemisch versorgt, um gute Zündbedingungen innerhalb der Vorkammer sicherzustellen. Im Rahmen dieser Arbeit werden die Gase aus dem Tank oberhalb des Flüssigkeitsspiegels zur Einstellung des Gemischs in der Vorkammer verwendet. Je nach Brennverfahren werden unterschiedliche Druckniveaus und Kraftstoffkonzentrationen für die Vorkammerspülung eingesetzt. Die verwendeten Vorkammern können ohne Anpassung am Zylinderkopf in modernen PKW-Motoren eingesetzt werden. Die Vorkammern werden am Vollmotor erprobt und thermodynamisch analysiert. Dabei können stabile Zündbedingungen bis λ = 1,95 im Teillastbereich gezeigt werden. Daneben werden auch optische Untersuchungen zur Charakterisierung der Vorkammerzündung durchgeführt. Dabei kommt sowohl ein optisch zugänglicher Motor als auch eine optisch zugängliche Einspritzkammer zum Einsatz. Letztere kann auch mit einem definierten Hintergrundgemisch betrieben werden. Mit diesem Aufbau lässt sich durch eine Kombination von Schlieren-Messtechnik und der Aufzeichnung des OH*-Radikals der Zündvorgang charakterisieren.<br
Keywords: Vorkammer; Vorkammerzündung; Pre-Chamber Ignition; jet ignition

Flame Luminesce in an Optically Accessible Engine with an Active Fuelled Pre-Chamber Ignition System - Russwurm, Tim; Wensing, Michael; Euchner, Lukas; Janas, Peter (21. Internationales Stuttgarter Symposium, 2021)
Homogeneous lean or diluted combustion can significantly increase the efficiency of SI engines. Active fuelled Pre-Chamber ignition systems can overcome the problem that common spark ignitions systems are incapable to ignite strongly diluted mixtures. In the research project LEANition, an active Pre-Chamber with an integrated pressure transducer was developed. The active fuelling is done by volatile components of gasoline fuel using an in-house developed fuelling system. To understand the combustion processes with active Pre-Chamber ignition, optical investigations of the flame luminescence are performed inside an optical accessible engine through a piston crown window. To record single cycles with high temporal resolution, an highspeed intensifier and a highspeed camera was used to reach an imaging frequency of 36 kHz. The selected engine speed is 1200 rpm. Both stochiometric composition and lean charges at Lambda = 1.8 in the cylinder are investigated regarding the ignition and combustion processes. In lean cylinder environments the jets from the Pre-Chamber entrain the surrounding gas and the ignition expands from the center of the jets to the remaining cylinder. In contrast to this, at stochiometric cylinder charges, the jets cross the cylinder bore at high speed, the cylinder combustion is induced from the outside of the cylinder bore inwards to the middle of the bore. Increased charge motion in the cylinder with imposed swirl decreases the combustion duration as the flame front reaches the area between the reactive jets faster.<br
Keywords: Pre-Chamber; Jet Ignition; Diluted combustion

Investigations on an active pre-chamber ignition system in a combustion chamber - Russwurm, Tim; Peter, Andreas; Strauß, Lukas; Rieß, Sebastian; Wensing, Michael (International Journal of Engine Research, 2022)
Pre-chamber ignition systems are one way to enable homogeneous lean or dilute combustion. Both strategies can significantly increase the efficiency of spark ignition engines. Spark initiated combustion in the pre-chamber produces hot gases that rapidly enter the cylinder and ignite the diluted charge at multiple points. Active ignition systems with fuel in the pre-chamber can directly influence the composition of the pre-chamber to ensure good ignition properties and sufficient ignition energy. This paper shows results from a novel test facility that enables investigations on the jet propagation of an active pre-chamber inside a constant pressure vessel. Thereby, the background mixture inside the vessel is variated between lambda = 1.0 and lambda = 2.0. With a special designed single-hole pre-chamber the flame propagation of a single pre-chamber jet is measured both in direction of the transfer port and perpendicular to this direction. Compared to spark ignition under equal ambient conditions (350 degrees C, 10 bar), the pre-chamber combustion propagates around eight times faster in direction of the transfer port and 60% faster in radial direction. Until lambda = 1.6, the flame propagation speed in radial direction can be kept on the level of a stoichiometric spark ignition. The simultaneous record of OH*-chemiluminescence and high-speed Schlieren imaging shows that the dominant ignition mechanism of a passenger-car sized pre-chamber is jet ignition according to the classification of Biswas. In stoichiometric cylinder conditions, a rich pre-chamber hampers the ignition in the main chamber whereas in lean operation points the scavenging of the pre-chamber with a rich lambda = 0.8 mixture is beneficial. These measurements indicate how the disrupted flame front of a pre-chamber jet increases the turbulence and enhances the flame propagation. The highest recorded propagation speed occurs in stoichiometric conditions both in the pre-chamber and in the combustion module.
CRIS-Team WoS Importer:2022-09-09

Investigations on lean and EGR-diluted combustion with active Pre-Chamber Ignition using a 1D-simulation model - Russwurm, Tim; Achenbach, Tobias; Wensing, Michael (International Conference on Ignition Systems for Gasoline Engines – International Conference on Knocking in Gasoline Engines, 2022)
Keywords: Pre-Chamber; Ignition; TJI

Liquid Organic Hydrogen Carriers as chemical hydrogen storage – Opportunities and challenges of reconversion into electricity with combustion engines - Durst, Alexander; Russwurm, Tim; Strauß, Lukas; Wensing, Michael (13. Tagung Gasfahrzeuge - eine nachhaltige Alternative, 2019)
Climate change is omnipresent and stricter laws to reduce carbon dioxide emissions are enforced. This work describes the potentials and challenges of the reconversion of hydrogen, stored in liquid organic carriers, into electricity by ICE. Hydrogen stored in LOHCs requires an enthalpy of 65 kJ/molH2 at a temperature level of 280-350 °C for direct dehydration without any intermediates. Therefore, an internal combustion engine is used, using the exhaust enthalpy for the dehydration of LOHC. The main advantages of this system are the possibility to store renewable energy, to reduce the carbon dioxide emission and thus making a ontribution to energy turnaround. The challenge lies in the fact that the enthalpy of the exhaust gases in efficient engines is too small to dehydrate a sufficient hydrogen mass flow from Dibenzyltoluol. For this reason, the engine runs on a mixture of hydrogen and methane. In order to find the best settings for the LOHC system, two operating strategies respectively engine settings are investigated. The first one is the strategy of the best overall efficiency, the second one is the strategy of the best renewable efficiency, what is similar to the lowest methane mass flow for constant conditions. The optimum overall efficiency is reached for the leanest possible combustion (approximately λ=2) and a centre of combustion MFB50 at 8° CA ATDC. But due to low energy losses, the exhaust enthalpy is small, therefore the percentage of hydrogen in the fuel is approximately 5 wt.% (≙ approximately 11,2% of the fuel energy). To increase the percentage of hydrogen at about 20 wt.% (≙ approximately 37,5% of the fuel energy) in the fuel and to minimise the methane flow, a stoichiometric combustion and a late centre of combustion MFB50 at 20° CA ATDC are favourable. Future concepts show potentials to reduce dehydration energy and especially the required temperature level so that a higher share of the exhaust enthalpy can be used and even better efficiencies can be achieve
Keywords: LOHC; Hydrogen; Combustion Enginge; Liquid Organic Hydrogen Carrier; Hydrogen Direct Injection

Measurement techniques for active pre-chamber ignition systems: optical experiments and thermodynamic evaluation - Russwurm, Tim; Peter, Andreas; Rieß, Sebastian; Wensing, Michael (Proceedings of the COMODIA2022, 2022)
Homogeneous lean or diluted combustion can significantly increase the efficiency of SI engines. These diluted engine charges suffer from poor ignitability and lead to unstable combustion. Actively fuelled pre-chamber ignition systems can overcome this problem with a high power ignition from a chemical reaction inside the pre-chamber. The active fuelling ensures good ignition conditions inside the pre-chamber even with high EGR rates or lean cylinder charges. The active fuelling is done by volatile components of gasoline fuel using an in-house developed fuelling system. This system is adapted to either high-EGR or lean combustion as the requirements for the scavenging systems are much dif-ferent in these two operation modes. This actively scavenged pre-chamber ignition system adds more parameters like quality, timing and quantity of the scavenging gas to the engine, so the correct calibration of these additional parameters is mandatory to optimize the combustion process. The pre-chamber is designed to fit a miniature pressure transducer to evaluate the combustion process inside the pre-chamber. Together with the other pressure transducers that are commonly mounted in research engines, a thermodynamic analysis of the combustion process is possible. Thus, a 1D-simulation model can be calibrated to evaluate unmeasured parameters like exhaust gas content and fuel-air-ratio inside the pre-chamber at ignition timing. To understand the combustion processes with active pre-chamber ignition systems, optical investigations of the flame luminescence are performed inside an optical accessible engine through a piston crown window. To record single cycles with high temporal resolution, a high speed intensifier and a high speed camera are used to reach an imaging frequency of 36 kHz. The selected engine speed is 1200 rpm. These measurements show the progress of the engine combustion through the cylinder under real engine conditions including charge motion. To gain deep insight into the ignition process of a pre-chamber, more detailed optical investigations are required. These measurements are performed inside an optically accessible combustion vessel with constant pressure. To analyse the jet ignition process, a special insert to this constantly scavenged chamber is developed to create a reactive environment but maintain the constant pressure during combustion. For these measurements, high speed schlieren images and the OH*-chemiluminescence are recorded simultaneously. With the superposition of these two optical techniques, the combustion progress can be visualized in detail. It reveals that the reactive jet from the pre-chamber shows only a very weak combus-tion signal, the main cylinder combustion is started by a secondary ignition inside these reactive jets. This visualisation of the combustion process without the influence of charge motion or pressure gradients enables to develop and calibrate a combustion model. The combination of optical measurements and the thermodynamic analysis can show the major interrelationships of the pre-chamber ignition system. To develop a combustion system for passenger cars, the optimisation of the entire system from the geometrical design of the pre-chamber to the active scavenging system is necessary. The paper contribution demonstrates the co-working of modern diagnostics and modelling in the development of advanced combustion systems.<br
Keywords: Active pre-chamber ignition; optical engine; high speed schlieren; jet ignition

Optical Investigations on the Jet Propagation of an Actively Fuelled Pre-Chamber Ignition System with Highspeed Schlieren Imaging - Russwurm, Tim; Peter, Andreas; Weiß, Lukas; Rieß, Sebastian; Wensing, Michael (THIESEL 2020.Thermo-and Fluid Dynamic Processes in Direct Injection Engines.8th-11th September, 2020)

Oxidation of soot in gasoline exhaust on Mn2O3 catalyst - Singer, Christian; Hahn, Christoph; Phan, Dai Q.; Russwurm, Tim; Wensing, Michael; Koegl, Matthias; Zigan, Lars; Kureti, Sven (Applied Catalysis A-General, 2023)
A Mn2O3 catalyst was investigated for soot oxidation in gasoline exhaust. Catalytic studies performed in model exhaust with Mn2O3/soot mixtures in tight contact showed efficient soot oxidation above 250 °C. This high performance was additionally confirmed on a gasoline engine test bench using a Mn2O3-coated particulate filter. The mechanism of the oxygen transport from the gas phase to soot was investigated by kinetic modeling of O2 adsorption and desorption as well as catalytic studies using 18O2. As a result, it was suggested that O2 dissociatively adsorbs on Mn2O3 followed by surface migration and transfer of oxygen to the soot at physical contact points between the two solids. The surface, sub-surface and bulk oxygen of the catalyst were also found to play a role. Enhanced participation of bulk oxygen appeared with declining O2 content due to partial reduction of Mn2O3 and formation of oxygen vacancies driving the oxygen mobility.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Gasoline exhaust; Isotopic labeling; Mechanism; Mn; Soot oxidation

Oxidation of soot in gasoline exhaust on Mn2O3 catalyst - Singer, Christian; Hahn, Christoph; Phan, Dai Q.; Russwurm, Tim; Wensing, Michael; Koegl, Matthias; Zigan, Lars; Kureti, Sven (Applied Catalysis A-General, 2023)
A Mn2O3 catalyst was investigated for soot oxidation in gasoline exhaust. Catalytic studies performed in model exhaust with Mn2O3/soot mixtures in tight contact showed efficient soot oxidation above 250 °C. This high performance was additionally confirmed on a gasoline engine test bench using a Mn2O3-coated particulate filter. The mechanism of the oxygen transport from the gas phase to soot was investigated by kinetic modeling of O2 adsorption and desorption as well as catalytic studies using 18O2. As a result, it was suggested that O2 dissociatively adsorbs on Mn2O3 followed by surface migration and transfer of oxygen to the soot at physical contact points between the two solids. The surface, sub-surface and bulk oxygen of the catalyst were also found to play a role. Enhanced participation of bulk oxygen appeared with declining O2 content due to partial reduction of Mn2O3 and formation of oxygen vacancies driving the oxygen mobility.<br

Pre-Chamber Ignition System for Diluted Combustion Processes with Active Fuelling by Volatile Fuel Components - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (Workshop ENCOM 2019, Waischenfeld, 16./17.10.2019, 2019)

Pre-chamber Ignition System for Homogeneous Lean Combustion Processes with Active Fuelling by Volatile Fuel Components - Schumacher, Moritz; Russwurm, Tim; Wensing, Michael (Ignition Systems for Gasoline Engines, 2018)

Pre-Chamber ignition system with active fuelling: an enabler for homogeneous lean and diluted combustion processes - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (14th International AVL Symposium on Propulsion Diagnostics, 2020)